Effect of fertigation and conservation tillage on soil properties and maize yield - Martínez Gamiño Miguel Ángel; Jasso Chaverria, Cesario; Osuna Ceja, Esteban Salvador; Reyes Muro, Luis; Huerta Díaz Jesús; Figueroa Sandoval Benjamín (Revista Mexicana de Ciencias Agrícolas, 2018)
During the spring-summer agricultural cycle of 2009- 2011 research was conducted in the Experimental Station San Luis from INIFAP in order to evaluate the effect of fertigation and conservation tillage on soil properties and maize yield. Three levels of nitrogen were tested: 200, 300 and 400 kg ha-1 and two for potassium: 100 to 200 kg ha-1. Land preparation was made with the system of conservation tillage. Corn H-358 was used. The experimental design was a randomized block with four replications. During the development of the crop plant samples were made to determine the concentration of nutrients in plant tissue and generate extraction curves of NPK. Soil samples were made to determine the percentage of organic matter and microbial biomass. The infiltration rate and soil strength was determined. At the end of each cycle, grain yield and its components were evaluated. When applying traditional doses of fertilization through drip irrigation and metered by phenological stage and with conservation tillage, maize yield increased 35% in relation to soil fertilization, irrigation by gravity and conventional tillage. Extraction curves NPK, were obtained; a basic tool for proper fertilization according to crop needs by phenological stage.